The Presidents, their lives, families, and great decisions (Indianapolis, Ind. : Curtis Pub. Co., 1980)
Articles taken from the "Saturday Evening Post", both about and by the Presidents of the United States.
Keywords: Presidents -- United States -- Biography; Presidents